2014
DOI: 10.1002/oby.20906
|View full text |Cite
|
Sign up to set email alerts
|

Increase in visceral fat per se does not induce insulin resistance in the canine model

Abstract: ObjectiveTo determine whether a selective increase of visceral adipose tissue content will result in insulin resistance.Design and MethodsSympathetic denervation of the omental fat was performed under general inhalant anesthesia by injecting 6-hydroxydopamine in the omental fat of lean mongrel dogs (n=11). In the conscious animal, whole-body insulin sensitivity was assessed by the minimal model (SI) and the euglycemic hyperinsulinemic clamp (SICLAMP). Changes in abdominal fat were monitored by magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
(63 reference statements)
3
11
0
Order By: Relevance
“…We have extensive experience using a well-established canine model to demonstrate that diets supplemented with lard induce insulin resistance (15,18) within a relatively short time frame (19). We have also shown that a diet supplemented with SO induces weight gain similar to that caused by a lard diet, but is not associated with impairments in SI (15).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have extensive experience using a well-established canine model to demonstrate that diets supplemented with lard induce insulin resistance (15,18) within a relatively short time frame (19). We have also shown that a diet supplemented with SO induces weight gain similar to that caused by a lard diet, but is not associated with impairments in SI (15).…”
Section: Discussionmentioning
confidence: 93%
“…Hyperinsulinemic compensation has been hypothesized to be a normal response to insulin resistance . Hyperinsulinemia can be driven by changes in insulin secretion and/or insulin clearance . Indeed, insulin resistance develops in LARD animals and, therefore, hyperinsulinemic compensation achieved by increased insulin secretion and/or decreased metabolic clearance rate of insulin is necessary to produce adequate glucose disposal.…”
Section: Discussionmentioning
confidence: 99%
“…They raise the question as to whether the findings obtained in mouse studies can be directly extrapolated to other mammalian species. Despite the finding that inflammation can also lead to metabolic impairment in other mammalian species (Basinska et al 2015), only a limited number of comparative studies of non-human primates and canines has explored the metabolic impact of adipose tissue inflammation (Chung et al 2014;Castro et al 2015;Bastien et al 2015). Thus, whether adipose tissue hosts immune cells in mammals other than rodents and primates and whether these immune cells have the ability to regulate metabolism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between diabetes mellitus and serum levels of IL-6 has been shown in dogs and the reduction of visceral obesity has been demonstrated to cause a drop in several pro-inflammatory chemotactic cytokines and growth factors (Bastien et al 2015) and insulin resistance (Lottati et al 2009) in dogs. Nonetheless, the lack of a causal link between visceral obesity and insulin resistance has also been shown in dogs (Castro et al 2015). Further, the clinical parameters that define insulin resistance in mice and humans are not optimal measures in dogs (Ader et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The independence of improvements in insulin sensitivity between tissues (hepatic vs. peripheral) is important in highlighting newer data. Traditionally thought to be associated with insulin resistance, increases in visceral adiposity are not necessarily associated with increases in insulin resistance 20 or outcomes following bariatric surgery 21 and there are conflicting reports in regards to correlations between visceral fat content and improvements in glucose homeostasis following surgery 22,23 . This further supports the idea that signaling in the liver (including pathways involved in insulin sensitivity) is an important player in diabetes remission.…”
Section: Insulin Sensitivity (Resistance)mentioning
confidence: 99%